Peningkatan Daya Saing Produk “RAYO” dengan Pelatihan Ragam Teknik dan Motif Rajut pada Sanggar Kerajinan Wanita Rangkiang Selayo - Verni Juita; Warnida Warnida; Fitriyeni Oktaviani (Warta Pengabdian Andalas, 2022)
Sanggar Rangkiang is a women’s group in Selayo village with a common interest in improving their family living standards. Through the group, they learn together how to master knitting skills. Using their little own pocket money, they try to buy the knitting material and turn it into various kinds of knitted products. Some have also successfully sold the products to their acquaintances through direct selling or personal approaches. Despite those achievements, however, this group has been facing critical challenges, such as limited product varieties, unstandardized product qualities, and lack of neat consistency, undermining the product’s potential to compete in the larger knitted products market. Due to this condition, the team of Universitas Andalas has provided knitting materials and conducted training series on various knitting techniques and models. The training was conducted through three sections the delivery of learning materials through lecturing, the application of learning materials, and counselling and monitoring through mentoring. After the training, the participants can produce a variety of good-quality products according to the given time target. Ultimately, the knitted products are expected to be sold in the larger market, paving the way for their business independence.